2008
DOI: 10.1021/es801832s
|View full text |Cite
|
Sign up to set email alerts
|

Competitive, Microbially-Mediated Reduction of Nitrate with Sulfide and Aromatic Oil Components in a Low-Temperature, Western Canadian Oil Reservoir

Abstract: Fields from which oil is produced by injection of sulfate-bearing water often exhibit an increase in sulfide concentration with time (souring). Nitrate added to the injection water lowers the sulfide concentration by the action of sulfide-oxidizing, nitrate-reducing bacteria (SO-NRB). However, the injected nitrate can also be reduced with oil organics by heterotrophic NRB (hNRB). Aqueous volatile fatty acids (VFAs; a mixture of acetate, propionate, and butyrate) are considered important electron donors in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 19 publications
(22 reference statements)
2
52
1
Order By: Relevance
“…S3 in the supplemental material). Although we did not detect nitrate reduction with xylenes, the use of m-xylene as an electron donor for nitrate reduction with accumulation of nitrite under mesophilic conditions has been reported previously (34,48).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…S3 in the supplemental material). Although we did not detect nitrate reduction with xylenes, the use of m-xylene as an electron donor for nitrate reduction with accumulation of nitrite under mesophilic conditions has been reported previously (34,48).…”
Section: Discussioncontrasting
confidence: 54%
“…This was confirmed by determination of MPNs of mNRB at 40°C (5 ϫ 10 5 ml Ϫ1 and 3 ϫ 10 7 ml Ϫ1 for 18PW and 14IW, respectively) and of tNRB at 60°C (45 ml Ϫ1 and 20 ml Ϫ1 for 18PW and 14IW, respectively). NRB in the MHGC field use low-molecular-weight oil components, especially toluene, as electron donors for nitrate reduction (33,34). Concentrated 18PW reduced 10 mM nitrate at 40°C with toluene and ethylbenzene, but not with benzene or xylenes, as the electron donor (see Fig.…”
Section: Activity Of Tnrb In Water Samples From the Mhgc Fieldmentioning
confidence: 99%
“…Our experimental design did not allow reliable determination of toluene and other alkyl-benzenes, which were depleted in all three columns. However, microcosm studies of MHGC oil incubated with produced water only (31) or with a produced water inoculum and medium (30) had previously indicated that hNRB prefer toluene and other alkyl benzenes as electron donors for nitrate reduction, whereas SRB used both toluene and other alkylbenzenes, as well as alkanes (30,31,44). Partial or complete inhibition of sulfate reduction in bioreactors S-LN and S-HN was likely responsible for the decreased use of alkanes under nitrate-reducing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…These migrate from injectors to producers, depending on the availability of toluene, the preferred electron donor of hNRB of the genus Thauera (30,31,44). In the absence of nitrate breakthrough, produced waters contain sulfide but no sulfate and are dominated by the presence of hydrogenotrophic methanogens (Methanoculleus, Methanolinea, and Methanocalculus) and the acetotrophic methanogen Methanosaeta (Table 2, 3-PW, 4-PW, and 10-PW; see Table S1 in the supplemental material).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation